(untitled) (Research, Society and Development, 2022)
In the fully digital workflow, intraorals, 3D printers and milling machines are used. Through the scanners it is possible to virtually register the patients, applying a digital impression, to later transfer the obtained data to the software, where the project will be carried out with the collaboration of the computer (CAD). The CAM part deals with the manufacturing stage of the restoration, with the help of a milling machine. This work aimed to carry out an integrative literature review about digital workflow in dental fixed prostheses. A search was performed in electronic databases Google Scholar, Scientific Electronic Library Online (SciELO) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using the keywords: “Dental Prosthesis Planning”, “Computer-assisted design”, “Dental Technology”. Subsequently, the abstracts of the articles were read to choose those relevant to the topic and, thus, proceed to the reading of the article itself. Priority was given to studies with a publication date between 2010 and 2022. CAD/CAM has been used in dentistry since the 1980s, with the aim of fabricating prosthetic restorations. This technology is called chairside when scanning is performed directly in the patient’s mouth and the rest in the clinic. The digital flow becomes a differential in cases of great complexity and aesthetically demanding. Despite the high cost of acquisition and the need for learning, its use must be considered in the daily routine of dental clinics, being viable for natural teeth and implants.